1993
DOI: 10.1111/j.1365-3032.1993.tb00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms are involved in the production of volatile kairomones affecting the host seeking behaviour of Diadromus pulchellus, a parasitoid of Acrolepiopsis assectella

Abstract: Experiments were carried out to determine the origin of dialkyl disulphides found in the larval frass of Acrolepiopsis assectella Zell. which enable the specialist parasitoid Diadromus pulchellus Wsm. to find its host. These kairomones are not specific: they are also found in the frass of the generalist Cacoecimorpha pronubana Hb. fed a leek-based diet. They are emitted only after the frass emerges from the gut. Bacteria are present in the gut of larvae and in their frass. The addition of antibiotics to the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…It has been shown that direct modifications, especially those made by Staphylococcus sp. on several amino acids such as leucine, isoleucine and valine, can produce a whole set of C4 and C5 components with different chemical functions, from aldehydes to their corresponding alcohols, acids and esters (Schulz and Dickschat 2007;Thibout et al 1993). This would explain the origin of most identified non-cyclic compounds reported in Table 2.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It has been shown that direct modifications, especially those made by Staphylococcus sp. on several amino acids such as leucine, isoleucine and valine, can produce a whole set of C4 and C5 components with different chemical functions, from aldehydes to their corresponding alcohols, acids and esters (Schulz and Dickschat 2007;Thibout et al 1993). This would explain the origin of most identified non-cyclic compounds reported in Table 2.…”
Section: Discussionmentioning
confidence: 86%
“…Aromatic compounds, like benzeneethanol, are produced by degradation of aromatic amino acids. Along with 3-hydroxy-2-butanone, 2,3-butanedione and 3-methyl-3-buten-1-ol, these are typical fermentation-associated substances (Leroy et al 2011a;Schulz and Dickschat 2007;Thibout et al 1993). Therefore, despite widespread distribution in the environment, S. xylosus remains a specific indicator of honeydew presence through its mVOC emissions modulated by the growth substrate.…”
Section: Discussionmentioning
confidence: 99%
“…This was done by comparing between the responses of C. marginiventris females towards odors from frass derived from Bt maize tissue and responses towards odors from frass derived from conventional maize tissue treated with the broad-spectrum antibiotic tetracycline. Previous studies showed that bacteria present in the gut and frass of insects are responsible for producing volatiles that are attractive to parasitoid females (Auger et al 1990;Thibout et al 1993Thibout et al , 1995, and that lepidopteran gut bacteria are generally susceptible to tetracycline (Visotto et al 2009). Our study is the first to question whether GM crops, including Bt maize, negatively affect chemical communication between foraging parasitoids and their hosts via alteration of host frass, an important source of odors that are useful for locating hosts at short ranges.…”
Section: Introductionmentioning
confidence: 99%
“…These authors also suggested that stable fly development depends on a live microbial community in the natural habitat and that fly females are capable of selecting an oviposition site based on the microbially derived stimuli that indicate the suitability of the substrate for larval development. Hymenoptera Thibout et al (1993Thibout et al ( , 1995 have identified sulphur containing volatiles such as alkyl disulphides (dimethyl Table 4 Semiochemically mediated interactions between bacteria and Diptera (Muscidae) P. D. Leroy et al disulphide and dipropyl disulphide) from bacteria (Bacillus sp. and Klebsiella oxytoca) which attract and help the parasitoid Diadromus pulchellus (Hymenoptera: Ichneumonidae) to locate its hosts Acrolepiopsis assectella (Table 5).…”
Section: Muscidaementioning
confidence: 99%
“…The mass production of bacteria at a low cost could be envisaged to use these microorganisms as a source of semiochemicals to attract and trap insects in field crops. Another option could be based on the use of bacterial semiochemicals to enhance the presence of auxiliaries in crops to protect: semiochemicals emitted by specific bacteria associated with the insect pests can, for example, increase the effectiveness of parasitoids and predators (Thibout et al 1993).…”
Section: Interactions Between Bacteria and Insectsmentioning
confidence: 99%